2012
DOI: 10.4085/1062-6050-47.6.06
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Tarsal Coalition in a National Collegiate Athletic Association Division I Basketball Player: A Case Report

Abstract: Objective To present a case of bilateral subtalar joint coalition in a National Collegiate Athletic Association Division I basketball player and the treatment plan that was used to manage the coalition from the beginning of conference play through the postseason. Background A 20-year-old male basketball athlete (height = 182.8 cm, mass = 83.4 kg) presented with bilateral subtalar joint tarsal coalition that became symptomatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 42 publications
0
2
0
2
Order By: Relevance
“…9 The surgical outcome of tarsal coalition was evaluated by many clinical studies with few reports of nonsurgical treatment outcome. 10 Jayakumar and Cowell reported that approximately 25–30% of their patients improved with casting. 6 In the study by Blockey on 30 rigid flatfeet, 2 the results after 2-year follow-up were 2 feet (6.6%) complete cure, 16 feet (53.4%) partial relapse, and 12 feet (40%) complete relapse.…”
Section: Discussionmentioning
confidence: 99%
“…9 The surgical outcome of tarsal coalition was evaluated by many clinical studies with few reports of nonsurgical treatment outcome. 10 Jayakumar and Cowell reported that approximately 25–30% of their patients improved with casting. 6 In the study by Blockey on 30 rigid flatfeet, 2 the results after 2-year follow-up were 2 feet (6.6%) complete cure, 16 feet (53.4%) partial relapse, and 12 feet (40%) complete relapse.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, Suits and Oliver used medial arch supports, joint mobilization, stretching, massage, foam rolling, and whirlpool, which allowed the athlete to continue to compete; however, there was no longer follow-up conducted. 9 Other studies mention conservative care by listing physical therapy interventions but fail to provide a protocol or reference evidence.…”
Section: Discussionmentioning
confidence: 99%
“…There is scarce information about clinical outcomes of coalition surgery in athletes; studies are mostly limited to small case series or case reports [13,15,38,42]. Elkus [6] reported excellent results in 20 athletes (25 feet) who underwent bar resection.…”
Section: Outcomes After Coalition Resectionmentioning
confidence: 99%